Imageless, Computer-Assisted Navigation Improves Acetabular Component Positioning Precision in Revision Total Hip Arthroplasty - Dundon, John M.; Paprosky, Wayne G.; Schwarzkopf, Ran; Barlow, Brian T.; Vigdorchik, Jonathan M. (The Journal of Hip Surgery, 2022)
Instability and dislocation can occur in up to one in four cases following revision total hip arthroplasty (THA), and optimal placement of components is critical in avoiding re-revision. Computer-assisted navigation can improve accuracy and precision of component placement in primary THA; however, its role in revision surgery is not defined. The purpose of our study was to evaluate the effect of computer-assisted navigation on component placement in revision THA. This study was a retrospective, multicenter cohort of 128 patients (69 imageless navigation, 59 conventional) who underwent revision THA between March 2017 and January 2019. An imageless computer navigation device was utilized in 69 of the 128 patients. Acetabular component placement and the proportion placed in a functional safe zone were compared between navigation-assisted and conventional THA groups. Mean anteversion increased significantly in both the navigation group (18.6 ± 8.5 degrees vs. 21.6 ± 7.8 degrees, p = 0.03) and the control group (19.4 ± 9.6 degrees vs. 21.2 ± 9.8 degrees, p = 0.03). Postoperatively, the proportion of acetabular components within the safe zone in the navigation group (inclination: 88%, anteversion: 84%) was mildly improved over the control group (83 and 69%, respectively). Variance in inclination improved significantly in both the control (50.6 vs. 112.4 degrees, p = 0.002) and navigation (46.2 vs. 141.1 degrees, p < 0.001) groups. Anteversion variance worsened in the control group (96.3 vs. 87.6 degrees, p = 0.36) but the navigation group showed improvement (61.2 vs. 72.7 degrees, p = 0.25). Postoperative variance was significantly better in the navigation group compared to the control group (p = 0.04). Utilizing imageless navigation in revision THAs results in more consistent placement of the acetabular component as compared to nonnavigated revision surgeries.
Keywords: revision total hip arthroplasty; functional safe zone; computer-assisted total hip arthroplasty; hip impingement; dislocation total hip arthroplasty